Breaking Barriers: Niqab-Wearing Female Students Challenging Stigma in Academia - Samsu, Samsu; Akib, Nashri; Mansur, Mansur; Syamsu, Khairunnisa; Amir, Abdul Muiz (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2025)
This study investigates the experiences of niqab-wearing female students at the State Islamic Institute of Kendari (Institut Agama Islam Negeri – IAIN Kendari), the sole public Islamic higher education institution in Southeast Sulawesi, as they navigate academic life amid prevailing social stigma and the absence of institutional policies regarding niqab usage. The niqab is frequently associated with stereotypes of exclusivity and extremism, and is often perceived as a barrier to social interaction and academic participation. Utilising a qualitative approach with a phenomenological design, data were collected through in-depth interviews, participant observation, and focus group discussions involving 15 female students who wear the niqab. The findings indicate that the lack of formal regulations concerning the use of the niqab generates ambiguity regarding institutional standards and student behavior. Despite these challenges, participants demonstrate resilience through adaptive strategies, such as using social media platforms for self-expression and solidarity. They also display emotional maturity in managing stigma while remaining active in academic and extracurricular activities. Drawing on Self-Presentation Theory and Social Adjustment Theory, the study reveals that niqab-wearing students employ friendliness, openness, humour, and academic achievement to counter negative perceptions. Social media further serves as a vital space for articulating perspectives and fostering community. This research highlights the need for inclusive policies in Islamic higher education and contributes to broader discussions on religious diversity, gender, and inclusivity within multicultural academic settings in Eastern Indonesia.